Perbandingan Kekuatan Beton Mengandung Agregat Kasar Buatan Semen Dan Agregat Aksar Buatan Geopolimer - Aulia, Siti Aja (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
The availability of natural coarse aggregate is decreasing due to excessive exploitation and rapid infrastructure growth. Therefore, an alternative artificial coarse aggregate is needed to replace natural aggregate in concrete production. This study aims to compare the compressive strength of concrete using natural coarse aggregate with concrete incorporating artificial coarse aggregate from cement paste (BABs) and artificial coarse aggregate from geopolymer (BABp). BABs aggregate is produced by mixing Portland cement and water, while BABp aggregate is made by combining fly ash with an alkaline activator (NaOH and Na₂SiO₃). Both types of aggregate are molded into cylinders, dried, crushed, and sieved to achieve the appropriate size as coarse aggregate. The compressive strength of concrete with aggregate substitution was tested at 7 and 28 days. At 7 days, concrete with BABp exhibited the highest compressive strength (41.18 MPa), followed by concrete with natural aggregate (38.28 MPa) and BABs (36.23 MPa). At 28 days, concrete with natural aggregate had the highest compressive strength (51.65 MPa), but concrete with BABp showed nearly equivalent results (51.51 MPa), while concrete with BABs maintained the lowest compressive strength (45.88 MPa).